2020
DOI: 10.1002/advs.201902743
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastrong and Highly Sensitive Fiber Microactuators Constructed by Force‐Reeled Silks

Abstract: Fiber microactuators are interesting in wide variety of emerging fields, including artificial muscles, biosensors, and wearable devices. In the present study, a robust, fast‐responsive, and humidity‐induced silk fiber microactuator is developed by integrating force‐reeling and yarn‐spinning techniques. The shape gradient, together with hierarchical rough surface, allows these silk fiber microactuators to respond rapidly to humidity. The silk fiber microactuator can reach maximum rotation speed of 6179.3° s−1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 45 publications
0
51
0
Order By: Relevance
“…In addition, the gland, with decreasing diameter, has been proven to be an outstanding actuator of the sophisticated spinning system. [5,9] It has been qualitatively demonstrated that a region of contracting geometry of the S-shaped duct of silk gland can induce stretching of protein molecules, phase separation, and self-assembly due to shear and elongation flow. [10][11][12][13][14][15] During the subsequent spinning process in air, the protein ultimately aggregates into fibers with spectacular and distinctive properties.…”
mentioning
confidence: 99%
“…In addition, the gland, with decreasing diameter, has been proven to be an outstanding actuator of the sophisticated spinning system. [5,9] It has been qualitatively demonstrated that a region of contracting geometry of the S-shaped duct of silk gland can induce stretching of protein molecules, phase separation, and self-assembly due to shear and elongation flow. [10][11][12][13][14][15] During the subsequent spinning process in air, the protein ultimately aggregates into fibers with spectacular and distinctive properties.…”
mentioning
confidence: 99%
“…Initially, the twisting technique was applied in the textile area to make ply‐yarns for improved mechanical property, but nowadays its application has been extended into various cutting‐edge fields, for example, sensor, [ 24 ] actuator, [ 25 ] and artificial muscle. [ 26 ] Especially for the strain sensor, it is available to achieve a sensitive, durable, and low‐hysteresis feature by tuning the twisting structure and the related working mechanism in the stretching–recovery process has been systematically discussed.…”
Section: Discussionmentioning
confidence: 99%
“…The most important is that they can provide a comfortable wearing experience and respond to humidity for the purpose of managing body temperature. Lin ( Lin et al, 2020 ), Jia ( Jia T. et al, 2019 ), and other researchers ( Wang W. et al, 2019 ; An et al, 2020 ) adopted a conventional spinning and twisting yarn technology to prepare silk fiber actuators. Studies have shown that these types of actuators can quickly expand and contract by water absorption-induced loss of hydrogen bonds within the silk proteins and the associated structural transformation, as shown in Figure 4A .…”
Section: Single Stimulus Response Smart Actuatorsmentioning
confidence: 99%